Dynamics of Franchise Business Independence: A Case Study of McDonald's in Indonesia Amidst the Israel-Palestine Conflict - Wenedy, Aaron; Toruan, Lucas Gabrielle Octory L; Pahlefy, Muhamad Reza; Maskilo, Othniel Haziel Surya (Peneliti.net, 2024)
This essay explores the challenges to the independence of franchise businesses, focusing on the 2023 McDonald's (McD) boycott controversy in Indonesia amid the Israel-Palestine conflict. Franchise business, as a method for expanding operations globally, faces intricate issues when global political events intersect with local sentiments. The text delves into the tensions arising from the Israeli McDonald's controversial actions and their repercussions on McD Indonesia, examining how franchise businesses navigate global guidelines while adapting to local market needs. The essay elucidates the multifaceted conflict between Israel and Palestine and its influence on McDonald's global operations. The controversy arises from McDonald's Israel providing free meals to the Israeli Defense Forces (IDF), sparking a divided reaction worldwide. The essay highlights the ensuing public debate and boycott calls in Indonesia, where McD Indonesia, owned by PT Rekso Nasional Food, became a focal point of discussion. The philosophical lens of axiological ethics is employed to analyze the societal stance on the McDonald's boycott. Axiology, centered on moral values shaping human actions, reveals that the boycott manifests as an expression of solidarity and justice. However, the essay also explores the nationalist sentiments underlying the boycott and emphasizes the need to assess its pragmatic impact on Indonesia's economy and the resolution of the Israel-Palestine conflict.The text emphasizes McDonald's Indonesia's independence, clarifying its non-affiliation with the policies of McDonald's globally, particularly in Israel. The company affirms its commitment to humanitarian values, demonstrated by a monetary contribution to Gaza. The essay scrutinizes the ethical dilemmas faced by investors amid the boycott, underscoring the need for businesses to align strategies with broader considerations in addressing franchise-related challenges. In conclusion, the essay underscores the complexity of relationships between global brand owners, local franchisees, and public opinions. It discusses how McDonald's Indonesia, by asserting its independence and humanitarian commitments, exemplifies the delicate balance franchise businesses must strike amidst global controversies. The analysis combines axiological ethics and pragmatic considerations, providing insights into the ethical values driving societal actions and evaluating the tangible impacts of such actions. The McDonald's case in Indonesia highlights the evolving dynamics of franchise businesses in navigating global and local challenges.